PERSONAL MORALITY AND ECONOMIC INTERESTS IN THEODORE DREISER’S THE FINANCIER - Mardanova Mohira Davron qizi (American Journals Publishing, 2025)
This article examines the complex interaction between personal morality and economic interests in Theodore Dreiser’s novel The Financier. The study analyzes how the protagonist, Frank Cowperwood, navigates financial ambition, ethical compromise, and social expectations within a rapidly developing capitalist society. Using textual analysis, the article evaluates the ways in which Dreiser illustrates the tension between individual moral responsibility and the pursuit of economic power. The findings show that Cowperwood’s actions are shaped not only by personal character but also by structural economic forces that redefine the boundaries of moral choice. The study concludes that The Financier provides a nuanced representation of moral ambiguity in modern economic life.
Keywords: Frank Cowperwood, morality, economic interests, capitalism, social ethics, Theodore Dreiser.